Pengaruh Inflasi, Birate, Volume Perdagangan Saham, dan Kurs Terhadap Indeks Harga Saham Gabungan pada Bursa Efek Indonesia Periode 2008-2017 - Eka Novitasari (Science of Management and Students Research Journal (SMS), 2020)
This study consisted of independent variables, namely inflation, birate, stock trading volume, exchange rate and the dependent variable, namely the joint stock price index. the formulation of the problem of how to influence the independent variable on the dependent variable simultaneously and partially in this study, the method used is a qualitative and quantitative descriptive method. The analytical tool used is statistics.In this study, the method used is qualitative and quantitative descriptive method. The analytical tool used is a statistical analysis tool consisting of multiple linear regression models, classic assumption tests, hypothesis testing and determinant coefficient.The object of research is inflation, birate, stock trading volume, and the exchange rate of the joint stock price index in 2008 to 2017 that are on the Indonesian stock exchange and bank Indonesia.Based on the results of the study assisted by the SPSS 20 device, the regression equation Y = 3,197 + 1,209 X_1 + -1,982X_2 + -0,026 X_3 + -0,196 X_4 + e produces the other side simultaneously obtaining the independent variable test (inflation, birate, stock trading volume, and the exchange rate does not have a significant effect on the dependent variable of the joint stock price index. the conclusions obtained from the F test (simultaneous) namely the independent variable inflation, birate, volume of stock trading, the exchange rate does not have a significant effect on the dependent variable of the joint stock price index. for the t test there is no significant effect.